Shanghai expo : an international forum on the future of cities - Winter, Tim, 1971- (Culture, economy and the social, 2012)
"In 2010 Shanghai hosted the largest, most spectacular and most expensive expo ever. Attracting a staggering 73 million visitors, and costing around US$45 billion dollars, Shanghai Expo broke the records in the history of world's fairs and universal expositions. With more than half of the world's population now living in cities, many of which face uncertain futures, this mega event confronted some of the key challenges facing humanity in the 21st Century, with its theme Better City, Better Life. Just two years after the Beijing Olympics, Shanghai Expo encapsulated a moment in history defined by China's rise as a global superpower, and by the multiple challenges associated with developing more sustainable cities. The thirteen essays here, written by a team of interdisciplinary researchers, offer a uniquely detailed analysis of this globally significant event. Chapters examine displays of futurity and utopia, the limitations of inter-cultural dialogue, and the ways in which this mega-event reflected its geo-political and cultural moment. Shanghai Expo also concentrates on the interplay between declarations towards urban sustainability, and the recent economic, demographic and socio-political trajectories of Shanghai and China more broadly. It will appeal to students and scholars of sociology, history, politics, international relations, economics, Asian studies, China studies, sustainability, and urban studies"--